Recent advances in kidney transplantation: a viewpoint from the Descartes advisory board. Issue 10 (12th January 2018) - Abramowicz, Daniel; Oberbauer, Rainer; Heemann, Uwe; Viklicky, Ondrej; Peruzzi, Licia; Mariat, Christophe; Crespo, Marta; Budde, Klemens; Oniscu, Gabriel C
ABSTRACT: Transplantation medicine is a rapidly evolving field. Keeping afloat of the published literature to offer the best clinical care to our patients is a daunting task. As part of its educational mission, the Descartes advisory board identified seven topics in kidney transplantation where there has been substantial progresses over the last years: kidney allocation within Eurotransplant; kidney exchange strategies; kidney machine perfusion strategies; the changing landscape of anti-human leukocyte antigen (HLA) antibodies; the new immunosuppressive drugs in the pipeline; strategies for immunosuppression minimization; and the continuous enigma of focal segmental glomerular sclerosis recurrence after transplantation. Here, we have summarized the main knowledge and the main challenges of these seven topics with the aim to provide transplant professionals at large with key bullet points to successfully understand these new concepts.